Strengthening of pre-loaded RC beams using sustainable ambient-cured FA/GGBS geopolymer mortar - Abdullah Y. Osman (22282813) (2024)
This study investigates the effect of using ambient-cured geopolymer mortar (GPM) made of fly ash (FA) and ground-granulated blast furnace slag (GGBS) as a sustainable strengthening material on the flexural behaviour of pre-loaded reinforced concrete (RC) beams. Ten RC beams were prepared, and then eight of them were loaded at different levels and strengthened with different depths using FA/GGBS-based GPM. The investigated parameters in this study include the effect of pre-loading level and strengthening depth on the ultimate moment capacity, midspan deflection, initial stiffness, toughness, and mode of failure. The obtained results of this study showed that strengthening 50% pre-loaded RC beams using GPM at a depth of 25 mm contributed to improving the moment capacity by about 10%. It was also found that using FA/GGBS-based GPM to strengthen RC beams with a thick layer of GPM affected the flexural behaviour of the strengthened beams negatively. Finally, an analytical model provided by the ACI code was implemented to predict the ultimate moment capacity and instantaneous deflection of the GPM-strengthened RC beams. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-024-00970-0